Conditional Cash Transfers : A New Paradigm for Combating Poverty in Latin America? - Pérez, Pablo Ernesto (2017)
Pérez and Brown analyze the strategies behind the implementation of Conditional Monetary Transfer Programs (CMTP) in Latin America since the 1990s. Those policies were a new attempt at engaging the pervasiveness of unemployment. In fact, the authors explain that these poli- cies come as an oddity since they have multiplied even after the so- called progressive governments. They attempt to study the different CMTP in the region and its main characteristics, providing a critical reflection on the diagnosis they rely on and on the policies themselves.